72 Key concepts for assessing treatment claims: a blog series by students 4 best evidence. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Carter, Emma; Ryan-Vig, Selena
Abstract : Objectives: Students 4 Best Evidence (S4BE) objectives were: to raise awareness of key concepts designed to help people assess claims about the effects of treatments; to encourage students to write blogs, providing an alternative platform for learning; and to promote critical thinking and discussion of the numerous treatment claims seen and heard every day. In 2013, an Informed Health Choices (IHC) project team published a list of 33 'Key Concepts'. The list was designed to be a starting point from which teachers and other intermediaries could develop resources to help people understand and apply the concepts. It is a 'living' document, subject to yearly review, which as at September 2017 lists 36 concepts. The overall aim was to produce a key resource which sought to help in the understanding and dissemination of these concepts. Method: We invited the S4BE community (via our monthly newsletter, social media and whilst on student electives at Cochrane UK) to write an explanatory blog on one of the 36 'Key Concepts'. Bloggers were encouraged to use 2 key sources for researching content for their blog: Testing Treatments interactive (TTi) which provides explanatory and illustrative resources linked to each key concept and the James Lind Library. Each of the blogs were then reviewed by Iain Chalmers of TTi, who provided support and feedback, assisting us in producing 'quality assured' blogs. Short videos explaining the concept were embedded into the blog, together with clear signposting to further learning resources. The blogs were published on the Students 4 Best Evidence (S4BE) website, promoted amongst our partners, highlighted in our monthly newsletter and disseminated via social media. Results: 19 students have written a total of 36 blogs, explaining each of the key concepts. As at 28 February 2018, 25 of these blogs have been published on the S4BE website, with a combined total of 62 635 views. Further information relating to the reach and commentary on social media platforms will be published in the final poster. An unanticipated result of this project was the engagement of several organisations wanting to translate the blogs and/or short videos. Translation into Portuguese, Spanish and German has all begun, with further enquiries from Croatian and Dutch groups. Conclusions: The remaining 11 blogs are due to be published prior to Evidence Live 2018, at which time further analysis will be carried out of the reach of the blogs/videos. The unintended result of generating interest in countries outside of the UK has been an encouraging development. Further discussion about disseminating the full series will be key to its continued reach, as well as ensuring the blogs are updated as the 'living' document is revised.